1996
DOI: 10.1172/jci118458
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to the G1 globular domain of the cartilage proteoglycan aggrecan can induce inflammatory erosive polyarthritis and spondylitis in BALB/c mice but immunity to G1 is inhibited by covalently bound keratan sulfate in vitro and in vivo.

Abstract: Earlier work from this laboratory showed that the human proteoglycan aggrecan from fetal cartilages can induce a CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…27 Removal of chondroitin 28 or keratin sulphate chains significantly enhances the immunogenicity of aggrecan and distinct regions within the N-terminal, globular (G)1 domain, have been linked with arthritis induction. 29 In particular, amino acids 84-103 from this region have been shown to contain the arthritogenic CD4 + T cell epitope (GRVRVNSAY) in both PGIA and in patients with rheumatoid arthritis. 30 Importantly, recent studies have shown that the activation of aggrecan-specific CD4 + T cells following B cell-mediated antigen presentation is crucial for the full development of PGIA.…”
Section: Discussionmentioning
confidence: 99%
“…27 Removal of chondroitin 28 or keratin sulphate chains significantly enhances the immunogenicity of aggrecan and distinct regions within the N-terminal, globular (G)1 domain, have been linked with arthritis induction. 29 In particular, amino acids 84-103 from this region have been shown to contain the arthritogenic CD4 + T cell epitope (GRVRVNSAY) in both PGIA and in patients with rheumatoid arthritis. 30 Importantly, recent studies have shown that the activation of aggrecan-specific CD4 + T cells following B cell-mediated antigen presentation is crucial for the full development of PGIA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental models and clinical studies indicate that autoimmunity directed against fibrocartilage proteins/proteoglycans, including aggrecan, can induce enthesitis and spondylitis (50)(51)(52)(53). The strong HLA-B27 association with AS indicates that autoimmunity is important in human AS, especially at sites of fibrocartilage (31).…”
Section: Molecular Mechanisms Pertaining To Immune Activation In Enthmentioning
confidence: 99%
“…ϩ T cells recognize epitopes on the G1 domain of aggrecan (20,21) and on the separate globular link protein (22). In a recent study, Zou et al (23) examined the CD4 ϩ immune response of synovial T cells to the G1 domain in AS and rheumatoid arthritis patients, indicating that the G1 domain of aggrecan might play a pathogenetic relevant role in the cellular autoimmune response in AS and rheumatoid arthritis.…”
Section: Identification Of Novel Human Aggrecan T Cell Epitopes In Hlmentioning
confidence: 99%